2023
DOI: 10.1371/journal.pone.0280723
|View full text |Cite
|
Sign up to set email alerts
|

The potential of eHealth for cancer patients–does COVID-19 pandemic change the attitude towards use of telemedicine services?

Abstract: Background Internet penetration worldwide has increased rapidly over the recent years. With this growth, modern information and communication technologies (ICT) have become increasingly important. They do not only change daily life but also patient-physician interaction and health related information search, which can be summarized as electronic Health (eHealth). eHealth was already known before the emergence of the coronavirus disease 2019 (COVID-19), but this pandemic substantially challenged health systems,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Studies reporting sharing intentions of (electronic) PHID in general for primary purposes found associations with several sociodemographic variables ( Table 7 ). For example, increased willingness was associated with achieving higher education, 67 , 70 someone in a healthcare occupation, 71 female gender, 72 older age, 72 and male gender. 59 However, it should be noted that female gender was confirmed to be a significant predictor based on a study involving 20,076 participants, while the other study that found men to be more willing involved a much smaller sample size (n = 170).…”
Section: Resultsmentioning
confidence: 99%
“…Studies reporting sharing intentions of (electronic) PHID in general for primary purposes found associations with several sociodemographic variables ( Table 7 ). For example, increased willingness was associated with achieving higher education, 67 , 70 someone in a healthcare occupation, 71 female gender, 72 older age, 72 and male gender. 59 However, it should be noted that female gender was confirmed to be a significant predictor based on a study involving 20,076 participants, while the other study that found men to be more willing involved a much smaller sample size (n = 170).…”
Section: Resultsmentioning
confidence: 99%
“…During the coronavirus disease 2019 pandemic, a need arose to develop methods for delivering patient care remotely [1,2]. The World Health Organization defines Telehealth as "the use of information and communication technologies (ICTs) to deliver health services at a distance" [3,4]. In this context, virtual or remote care is a practical solution to offer essential services during social distancing and reduce non-essential clinical services [1,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve and continue going forward, the deep-down study of biomarkers in healthy and ill people during long periods of time is considered to be of paramount importance. In this regard, the promotion of e-Health philosophy, carried out by international organizations, has been an important spearhead [1]. This approach aims to achieve almost passive monitoring of people via nontraditional medical inspections (e.g., point of care), avoiding unnecessary tests and reducing costs.…”
Section: Introductionmentioning
confidence: 99%